Three - dimensional fluid attenuated inversion recovery sequence on 3 tesla magnetic resonance imaging in cranial nerve pathologies: two case reports - Thuyet, Dinh Van; Anh, Nguyen Van; Thu, Nguyen Viet; Nhan, Nguyen Thi; Dung, Bui Van (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
ABSTRACT Three - dimensional fluid attenuated inversion recovery sequence (3D-FLAIR) was introduced as a practical sequence which helps to reduce the cerebrospinal fluid pulsation and flow artefacts of conventional 2D acquisition and brings contiguous slices, ability in reformatting in variable planes which are typical features of 3D acquisition. 3D - FLAIR has been applied on assessing several neurologic pathologies. In this article, we introduce the application of 3D - FLAIR sequence without contrast enhancement on detecting abnormalities of cranial nerve pathology by presenting two cases, acute vestibular neuritis and facial nerve palsy. We suggest that 3D - FLAIR is the relatively useful sequence in detecting cranial nerve pathologies.